Annealing and temperature coefficient study of type ia fibre bragg gratings inscribed under strain and no strain - implications to optical fibre component reliability - Kalli, Kyriacos; Simpson, George D.; Webb, David J. (My University, 2006)
The annealing properties of Type IA Bragg gratings are investigated and compared with Type I and Type IIA Bragg gratings. The transmission properties (mean and modulated wavelength components) of gratings held at predetermined temperatures are recorded from which decay characteristics are inferred. Our data show critical results concerning the high temperature stability of Type IA gratings, as they undergo a drastic initial decay at 100°C, with a consequent mean index change that is severely reduced at this temperature However, the modulated index change of IA gratings remains stable at lower annealing temperatures of 80°C, and the mean index change decays at a comparable rate to Type I gratings at 80°C. Extending this work to include the thermal decay of Type IA gratings inscribed under strain shows that the application of strain quite dramatically transforms the temperature characteristics of the Type IA grating, modifying the temperature coefficient and annealing curves, with the grating showing a remarkable improvement in high temperature stability, leading to a robust grating that can survive temperatures exceeding 180°C. Under conditions of inscription under strain it is found that the temperature coefficient increases, but is maintained at a value considerably different to the Type I grating. Therefore, the combination of Type I and IA (strained) gratings make it possible to decouple temperature and strain over larger temperature excursions.
Keywords: Bragg gratings; Optical fibers; Reliability; Fibers